2015
DOI: 10.1155/2015/207491
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Aggressive Environment on the Damage of a Glass Polyester Composite Developed by Hand Layup Process

Abstract: This work treats the behavior of a glass fibre/unsaturated polyester (UP) composite with structural defects subjected to the attack of two corrosive solutions: H2SO4and NaOH. The gravimetric analysis, the uptake mass of the resin, and the interfaces in the composite are established according to the proportion of the matrix/composite. The obtained results showed that, in the acidic solution, the glass fibre and the fibre/matrix interface absorption share is more significant than the alkaline solution. While the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Degradation of the composite was therefore monitored in an outdoor environment with fluctuations in temperature and relative humidity (RH) (12–40 °C, 30–100% RH, up to 90 days [ 5 , 6 ]). Elevated temperature is often used in the laboratory to speed up tests in air (250 °C, 180 days [ 7 ]), water (ambient temperature, 180 days [ 8 ] or 50 °C, 100 days [ 9 ]), salt water or seawater (30–60 °C, up to 810 days [ 10 , 11 , 12 , 13 ]), and alkaline and acidic solutions (room temperature, 5 and 50 days [ 14 ]). The above research found that the water absorption of fiberglass composites increased with increasing temperature for environments with moisture, water, and seawater.…”
Section: Introductionmentioning
confidence: 99%
“…Degradation of the composite was therefore monitored in an outdoor environment with fluctuations in temperature and relative humidity (RH) (12–40 °C, 30–100% RH, up to 90 days [ 5 , 6 ]). Elevated temperature is often used in the laboratory to speed up tests in air (250 °C, 180 days [ 7 ]), water (ambient temperature, 180 days [ 8 ] or 50 °C, 100 days [ 9 ]), salt water or seawater (30–60 °C, up to 810 days [ 10 , 11 , 12 , 13 ]), and alkaline and acidic solutions (room temperature, 5 and 50 days [ 14 ]). The above research found that the water absorption of fiberglass composites increased with increasing temperature for environments with moisture, water, and seawater.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the exposure time was shown to be a determinant of the flexural properties. Moreover, Belloul et al [ 53 ] presented the behavior of the glass fiber/unsaturated polyester (UP) composite with structural defects subjected to the attack of two corrosive solutions: H 2 SO 4 and NaOH. The resistance and ductility losses revealed by the mechanical tests of the samples immersed in the two mediums of immersions are the result of a complex mechanism degradation implementing several phenomena such as the resin hydrolysis, the fiber corrosion, and the degradation of the fiber/matrix interface, in addition to the structural defects due to the implementation technique.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of bubble based degradation on the physical and structural properties of single wall carbon nanotube (SWCNT)/epoxy resin composite samples was investigated by Hashemi and Mousavi [ 56 ]. Additionally, Belloul et al [ 53 ] underlined that the presence of the pores (of rather significant size) in the material after its elaboration influences the diffusion kinetics of the acid and alkaline solutions and contributes to the mechanical degradation of the material. Moreover, air bubbles appeared on the surface, which made it rougher.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the production of the part in harsh environments can lead to the degradation of its mechanical properties due to its exposure. An example of this degradation is the corrosion of glass fibers in the polyester matrix when exposed to NaOH [19]. The most used matrices are epoxy and polyester because they cure at room temperature.…”
Section: Hand Lay-upmentioning
confidence: 99%